The Moderating Effect of Store Format on the Relationships Between ICT, Innovation and Sustainability in Retailing - Marín-García, Antonio; Gil-Saura, Irene; Ruiz-Molina, María-Eugenia; Berenguer-Contrí, Gloria (Frontiers in Psychology, 2021)
Innovation and sustainability are postulated as key variables for the future of large commercial distribution. In addition, the development of ICT solutions, and especially those related to Artificial Intelligence (i.e. Just Walk Out, Intelligent Retail Lab) and digitization, are particularly relevant factors in the current pandemic scenario in which retail companies operate. These tools are essential to face the derived changes in commercial relations, especially between companies and consumers. For all these reasons, this work aims to examine the effect of ICT, as a driving factor for innovation and its direct and indirect impact on sustainability in retailing. Furthermore, this study takes into account the eventual differences in these relationships according to the types of store formats. To achieve the aforementioned objective, a theoretical model is proposed that is tested through an empirical study carried out on a sample of 510 consumers of three store formats of grocery retail establishments (i.e. hypermarkets, supermarkets and discount stores) in Spain. For the analysis of the data obtained, the partial least squares (PLS) regression technique and the Multigroup Analysis were used. The results obtained confirm the direct and indirect effect of ICT on innovation and sustainability in grocery retailing. In addition, the results indicate that consumers unequally perceive the technological progress of companies. These differences are greater between discount stores versus hypermarkets and supermarkets. The larger the size of the store format, the higher the incidence of ICT in relation to innovation. Therefore, it is vital to take ICT into consideration, where Artificial Intelligence is imperative for the growth and development of sustainable competitive advantages in retail companies.